Does home oxygen therapy (HOT) in addition to standard care reduce disease severity and improve symptoms in people with chronic heart failure? A randomised trial of home oxygen therapy for patients with chronic heart failure - Andrew L Clark (Health Technology Assessment, 2015)
Background: Home oxygen therapy (HOT) is commonly used for patients with severe chronic heart failure (CHF) who have intractable breathlessness. There is no trial evidence to support its use. Objectives: To detect whether or not there was a quality-of-life benefit from HOT given as long-term oxygen therapy (LTOT) for at least 15 hours per day in the home, including overnight hours, compared with best medical therapy (BMT) in patients with severely symptomatic CHF. Design: A pragmatic, two-arm, randomised controlled trial recruiting patients with severe CHF. It included a linked qualitative substudy to assess the views of patients using home oxygen, and a free-standing substudy to assess the haemodynamic effects of acute oxygen administration. Setting: Heart failure outpatient clinics in hospital or the community, in a range of urban and rural settings. Participants: Patients had to have heart failure from any aetiology, New York Heart Association (NYHA) class III/IV symptoms, at least moderate left ventricular systolic dysfunction, and be receiving maximally tolerated medical management. Patients were excluded if they had had a cardiac resynchronisation therapy device implanted within the past 3 months, chronic obstructive pulmonary disease fulfilling the criteria for LTOT or malignant disease that would impair survival or were using a device or medication that would impede their ability to use LTOT. Interventions: Patients received BMT and were randomised (unblinded) to open-label LTOT, prescribed for 15 hours per day including overnight hours, or no oxygen therapy. Main outcome measures: The primary end point was quality of life as measured by the Minnesota Living with Heart Failure (MLwHF) questionnaire score at 6 months. Secondary outcomes included assessing the effect of LTOT on patient symptoms and disease severity, and assessing its acceptability to patients and carers. Results: Between April 2012 and February 2014, 114 patients were randomised to receive either LTOT or BMT. The mean age was 72.3 years [standard deviation (SD) 11.3 years] and 70% were male. Ischaemic heart disease was the cause of heart failure in 84%; 95% were in NYHA class III; the mean left ventricular ejection fraction was 27.8%; and the median N-terminal pro-B-type natriuretic hormone was 2203 ng/l. The primary analysis used a covariance pattern mixed model which included patients only if they provided data for all baseline covariates adjusted for in the model and outcome data for at least one post-randomisation time point (n = 102: intervention, n = 51; control, n = 51). There was no difference in the MLwHF questionnaire score at 6 months between the two arms [at baseline the mean score was 54.0 (SD 18.4) for LTOT and 54.0 (SD 17.9) for BMT; at 6 months the mean score was 48.1 (SD 18.5) for LTOT and 49.0 (SD 20.2) for BMT; adjusted mean difference –0.10, 95% confidence interval (CI) –6.88 to 6.69; p = 0.98]. At 3 months, the adjusted mean MLwHF questionnaire score was lower in the LTOT group (–5.47, 95% CI –10.54 to –0.41; p = 0.03) and breathlessness scores improved, although the effect did not persist to 6 months. There was no effect of LTOT on any secondary measure. There was a greater number of deaths in the BMT arm (n = 12 vs. n = 6). Adherence was poor, with only 11% of patients reporting using the oxygen as prescribed. Conclusions: Although the study was significantly underpowered, HOT prescribed for 15 hours per day and subsequently used for a mean of 5.4 hours per day has no impact on quality of life as measured by the MLwHF questionnaire score at 6 months. Suggestions for future research include (1) a trial of patients with severe heart failure randomised to have emergency oxygen supply in the house, supplied by cylinders rather than an oxygen concentrator, powered to detect a reduction in admissions to hospital, and (2) a study of bed-bound patients with heart failure who are in the last few weeks of life, powered to detect changes in symptom severity. Trial registration: Current Controlled Trials ISRCTN60260702. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 19, No. 75. See the NIHR Journals Library website for further project information.